Association between metabolic syndrome and liver histology among NAFLD patients without diabetes. Issue 1 (1st November 2016) - Kanwar, Pushpjeet; Nelson, James E; Yates, Katherine; Kleiner, David E; Unalp-Arida, Aynur; Kowdley, Kris V
Abstract : Background: Metabolic syndrome (MetS) and obesity are associated with non-alcoholic fatty liver disease (NAFLD). The aim of this observational study was to examine the relationship of MetS and a diagnosis of non-alcoholic steatohepatitis (NASH) in patients without diabetes in the NASH Clinical Research Network (CRN). Methods: Clinical, demographic, histological, laboratory and anthropometric data were collected on 356 adult patients without diabetes with NAFLD. Obesity was defined as body mass index ≥30.0. MetS was determined using the National Cholesterol Education Program-Adult Treatment Panel III (NCEP ATPIII) 2001 criteria to include 3 or more of the following: increased waist circumference, elevated triglycerides, reduced high-density lipoprotein cholesterol, hypertension and elevated fasting blood glucose. Results: Most patients were obese (71%) and had MetS (67%). Obesity was more prevalent among patients with MetS (80% vs 52%; p≤0.001). Markers of insulin resistance such as homoeostasis model assessment of insulin resistance (6.5 vs 4.9, p≤0.001) were higher among those with MetS compared with those without MetS. Histologically, patients without MetS had higher hepatocellular (p=0.04) and reticuloendothelial system iron (p=0.04). Patients with MetS were more likely to have severe hepatic steatosis (p=0.04) and chronic portal inflammation (p=0.01). On multiple logistic regression analysis, patients with definite NASH were almost 2.5 times more likely to have MetS than those without definite NASH (OR=2.41, p=0.01). Conclusions: MetS is common in patients without diabetes with NAFLD and is associated with greater insulin resistance, hepatic steatosis and portal inflammation. While patients without MetS have greater iron overload, patients with MetS may have an increased propensity to have NASH. Therefore, presence of MetS in patients without diabetes with NAFLD may serve as a potential criterion for liver biopsy. Trial registration number: NCT00063622; Pre-results.